The new union avoidance internationalism. (1st January 2019) - Logan, John
Abstract : Since the 1950s, large management-side law firms have helped corporations in the USA resist union organising campaigns. Their sophisticated techniques and aggressive tactics have made it extraordinarily difficult for unions to organise in the private sector. Over the past decade, several large law firms that specialise in union avoidance have internationalised their operations, opening offices in Latin America, Europe and Asia, forming international alliances and using global standards to attack labour organisation and undermine labour rights. This article analyses the global union avoidance activities of the two largest management-side labour law firms in the USA: Littler Mendelson and Ogletree Deakins.